The role of the origin country in migration aspirations: a cross‐national comparison of Master students in Portugal and the Netherlands - Jong, Petra Wieke (2020)
With this comparative study, we aim for a better understanding of the role of the origin country in shaping migration aspirations. Using experimental data collected among a sample of Master students in Portugal and the Netherlands, we tested whether the impact of labour market and welfare state-related factors on migration aspirations varied between these two origin countries. In line with our expectation, potential gains of migration in terms of job opportunities and wages had a stronger positive impact on migration aspirations for the Portuguese as compared with the Dutch respondents. For Portugal and the Netherlands alike, migration aspirations were lower when the level of unemployment benefits in the destination country was lower than in the origin country. Our findings indicated that conditions in the origin country, as well as the individual's life stage, shape which characteristics of the destination country are most important for migration aspirations.